2018
DOI: 10.5114/ceji.2018.74873
|View full text |Cite
|
Sign up to set email alerts
|

Association of the TNF-α, IL-2, and IL-2RB gene variants with susceptibility to psoriasis in a Turkish cohort

Abstract: Aim of the studyThe aim of this study was to investigate the role TNF-α, IL-2, and IL-2RB variants in psoriasis (Ps) and to evaluate the association between these variants and clinical features.Material and methodsA total of 74 psoriatic patients and 74 healthy individuals were genotyped for these variants by PCR and/or RFLP.ResultsThe AA genotype of TNF-α (–308) was significantly more common in the patients (p = 0.013). TNF-α (–238) AA genotype was significantly increased in the patients (p = 0.028), while th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 37 publications
(40 reference statements)
0
7
0
Order By: Relevance
“…Table 1 illustrates the studies including −238 G/A rs361525 polymorphism. Out of 24 articles [ 20 , 21 , [23] , [24] , [25] , [26] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] ] that include 26 studies, fourteen studies were reported in Caucasians, eight in Asians, and four in mixed populations. Out of 26 studies, thirteen studies reported patients with psoriasis vulgaris, eight with psoriatic arthritis, four with psoriasis, and one with generalized pustular psoriasis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 illustrates the studies including −238 G/A rs361525 polymorphism. Out of 24 articles [ 20 , 21 , [23] , [24] , [25] , [26] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] ] that include 26 studies, fourteen studies were reported in Caucasians, eight in Asians, and four in mixed populations. Out of 26 studies, thirteen studies reported patients with psoriasis vulgaris, eight with psoriatic arthritis, four with psoriasis, and one with generalized pustular psoriasis.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have investigated the relationship of single nucleotide polymorphism (SNP) of rs 361525 , rs 1800629 , rs 1799724 , 1800630 , and rs 1799964 in psoriasis cases compared to controls with different results [ [20] , [21] , [22] , [23] , [24] , [25] , [26] ]. Six meta-analyses [ [27] , [28] , [29] , [30] , [31] , [32] ] reported TNF-α polymorphisms in psoriasis cases.…”
Section: Introductionmentioning
confidence: 99%
“…48 TNF-a gene variants have been widely studied and previous findings show relationships between TNF-a gene variants and the development of autoimmune diseases, infectious diseases, and cancer. 49,50 In the present study, TNF-a gene polymorphisms were studied in SARS-CoV-2 infection. Only the c.27C.T variant of the TNF gene was seen in one patient with mild clinical manifestations.…”
Section: Discussionmentioning
confidence: 99%
“…IL-2 is a cell growth factor with various immunoregulatory functions and biological characteristics, secreted mostly by activated helper T lymphocytes [ 71 , 72 ]. Elevated serum IL-2 levels are associated with significant disease progression in many autoimmune diseases and cancers, including melanoma, autoimmune hepatitis, and systemic lupus erythematosus [ 73 , 74 ].…”
Section: Discussionmentioning
confidence: 99%